2013
DOI: 10.1152/ajpendo.00615.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 5 modulates STAT3 and androgen receptor activation through phosphorylation of Ser727 on STAT3 in prostate cancer cells

Abstract: Cyclin-dependent kinase 5 (Cdk5) is known to regulate prostate cancer metastasis. Our previous results indicated that Cdk5 activates androgen receptor (AR) and supports prostate cancer growth. We also found that STAT3 is a target of Cdk5 in promoting thyroid cancer cell growth, whereas STAT3 may play a role as a regulator to AR activation under cytokine control. In this study, we investigated the regulation of Cdk5 and its activator p35 on STAT3/AR signaling in prostate cancer cells. Our results show that Cdk5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…Subsequently, we found that the abnormal activation of Cdk5 triggered by intracellular calcium increase is involved in the apoptosis of prostate cancer cells [22]. Recently, our data also showed that a physiological activation of Cdk5 can phosphorylate and stimulate the androgen receptor and STAT3 and the growth of prostate cancer is therefore regulated [13,23]. Brown et al also indicate that ATRA-induced cell differentiation is correlated with the change in intracellular calcium [24].…”
Section: Introductionmentioning
confidence: 53%
“…Subsequently, we found that the abnormal activation of Cdk5 triggered by intracellular calcium increase is involved in the apoptosis of prostate cancer cells [22]. Recently, our data also showed that a physiological activation of Cdk5 can phosphorylate and stimulate the androgen receptor and STAT3 and the growth of prostate cancer is therefore regulated [13,23]. Brown et al also indicate that ATRA-induced cell differentiation is correlated with the change in intracellular calcium [24].…”
Section: Introductionmentioning
confidence: 53%
“…It has also been documented that different CDKs may contribute specifically to different tumor types in humans (17,18). CDK5, an atypical CDK that was previously considered to function in processes unrelated to cell-cycle regulation, has been shown to play a fundamental role in several kinds of carcinomas including breast, lung, prostate, multiple myeloma, and pancreatic cancers (39)(40)(41)(42)(43). However, the potential role of CDK5 in gastric cancer has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that CDK5 in fact plays an inhibitory role in gastric tumorigenesis. The kinase activity of CDK5 has been thought to mediate carcinogensis of certain nongastric cancer types (39)(40)(41)(42)(43). Our previous studies indicated that nuclear CDK5 can function as a cell-cycle suppressor in the nervous system (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, STAT3 becomes activated following cell stimulation by a cytokine or growth factor, while in cancer cells STAT3 is often deregulated. Cdk5 interacts with and phosphorylates STAT3 at Ser-727, which is necessary for MTC and prostate cancer cells proliferation [27, 28]. STAT3-target genes are indeed induced upon Cdk5 activation.…”
Section: Molecular Links Between Cdk5 and The Cell Cyclementioning
confidence: 99%
“…STAT3-target genes are indeed induced upon Cdk5 activation. Importantly, prostate cancer cells and prostate cancer patient tumors express Cdk5, p35 and phosphorylated Ser-727 STAT3 [28, 29]. It would be interesting to define the determinants for Cdk5-dependent phosphorylation of Rb versus STAT3.…”
Section: Molecular Links Between Cdk5 and The Cell Cyclementioning
confidence: 99%